Apšereniš: Slavnost u příležitosti postřižin - Segerová, Vendula (Lidé města, 2000)
"Upsherenish" a yiddish word for "haircutting" is a beautiful custom marking the third birthday of a Jewish boy, as well as his formal introduction to Jewish education and practice. The Torah compares man to a tree. A tree and a person both grow from a small seed, extend branches, reach maturity, and bear fruit. During the first three years of a tree's life, its fruit may not be cut for use. So too, a little boy's hair is not cut during his first three years. The article is divided into seven parts. The first part explains from the religious and historic point of view the origin of the custom. Second part is about importance attached to the first haircutting ceremony. Parts three, four and five are about age of the boy that can vary, date and choice of the place of this beautiful Jewish tradition. Part six describes the structure of the ceremony. Before the ceremony is explained to the boy the importance of the three years birthday connected with the first haircutting and leaving the "pe´ot," wearing always the "kippa" and beginning of the age of education. During the ceremony all his hair is cut mostly by his father and present man. The final part of the article shows a first haircutting ceremony of the son of rabi of Chabad N.C. in Prague, June 2000. It describes the custom, the birthday party and also the reflection of this tradition by a non-chasidic Jews.